Pembaharuan Dalam Sistem Pembagian Waris Secara Proporsional - Faiqah Nur Azizah (JOURNAL of LEGAL RESEARCH, 2021)
The purpose of this research is to identify and analyze the concept and legitimacy of reform in the Islamic inheritance distribution system in relation to men and women. The portion determined in QS al-Nisâ' verses 11-12 concerning the division of inheritance and the party entitled to receive the inheritance is regulated in detail, with implications for the ijtihad of scholars who position the verse as a qat'iyu al-Wurud verse (certainly the origin of the syar'i) and qat'iyu al-Dalâlah verse (definite designation on a certain meaning). The presence of the concept of renewal in the proportional inheritance distribution system answers the ulama's previous rigidity in conducting ijtihad. This study employs a qualitative research method in conjunction with a literature review. According to the study's findings, reforms in the Islamic inheritance distribution system that are proportional to men and women can be implemented. Given the very dynamic nature of law and Islam as a religion of mercy for the universe, it responds to this dynamic through the concept of ijtihad for religious leaders, judges, and the government in order to answer the problems faced by society based on the context of the times, conditions, time, and place.